Activation of AMP-Activated Protein Kinase-Sirtuin 1 Pathway Contributes to Salvianolic Acid A-Induced Browning of White Adipose Tissue in High-Fat Diet Fed Male Mice - Lai, Jianfei; Qian, Qianyu; Ding, Qinchao; Zhou, Li; Fu, Ai; Du, Zhongyan; Wang, Cui; Song, Zhenyuan; Li, Songtao; Dou, Xiaobing (Frontiers in Pharmacology, 2021)
Background: Salvianolic acid A (Sal A), a natural polyphenolic compound extracted from Radix Salvia miltiorrhiza (Danshen), exhibits exceptional pharmacological activities against cardiovascular diseases. While a few studies have reported anti-obesity properties of Sal A, the underlying mechanisms are largely unknown. Given the prevalence of obesity and promising potential of browning of white adipose tissue to combat obesity, recent research has focused on herbal ingredients that may promote browning and increase energy expenditure. Purpose: The present study was designed to investigate the protective antiobesity mechanisms of Sal A, in part through white adipose browning. Methods: Both high-fat diet (HFD)-induced obese (DIO) male mice model and fully differentiated C3H10T1/2 adipocytes from mouse embryo fibroblasts were employed in this study. Sal A (20 and 40 mg/kg) was administrated to DIO mice by intraperitoneal injection for 13-weeks. Molecular mechanisms mediating effects of Sal A were evaluated. Resluts: Sal A treatment significantly attenuated HFD-induced weight gain and lipid accumulation in epididymal fat pad. Uncoupling protein 1 (UCP-1), a specialized thermogenic protein and marker for white adipocyte browning, was significantly induced by Sal A treatment in both white adipose tissues and cultured adipocytes. Further mechanistic investigations revealed that Sal A robustly reversed HFD-decreased AMP-activated protein kinase (AMPK) phosphorylation and sirtuin 1 (SIRT1) expression in mice. Genetically silencing either AMPK or SIRT1 using siRNA abolished UCP-1 upregulation by Sal A. AMPK silencing significantly blocked Sal A-increased SIRT1 expression, while SIRT1 silencing did not affect Sal A-upregulated phosphorylated-AMPK. These findings indicate that AMPK was involved in Sal A-increased SIRT1. Conclusion: Sal A increases white adipose tissue browning in HFD-fed male mice and in cultured adipocytes. Thus, Sal is a potential natural therapeutic compound for treating and/or preventing obesity.